Order flow volatility and equity costs of capital - CHORDIA, Tarun (Institutional Knowledge at Singapore Management University, 2019)
We propose that the volatility of order flow is a proxy for costs of information asymmetry, as order flow volatility varies positively with parameters that also influence adverse selection costs of trading. Empirically, order flow volatility is significantly higher prior to earnings or merger announcements when information asymmetry is likely to be elevated. Levels of and shocks to order flow volatility are positively and significantly correlated with existing illiquidity proxies, and strongly predict stock returns in the cross section. The impact of order imbalance volatility shocks on stock prices is reflected within one month in large, visible stocks, but takes up to three months to be fully reflected in small, "neglected" stocks.